Self-driven all-inorganic perovskite microplatelet vertical Schottky junction photodetectors with a tunable spectral response. Issue 20 (22nd April 2020) - Gui, Pengbin; Li, Jiashuai; Zheng, Xiaolu; Wang, Haibing; Yao, Fang; Hu, Xuzhi; Liu, Yongjie; Fang, Guojia
Abstract : An all-inorganic perovskite self-driven vertical Schottky junction photodetector with a tunable spectral response is reported. Abstract : Wavelength-selective perovskite photodetectors (PDs) have many applications in optoelectronic fields, such as machine vision, imaging and full-color displays. However, the instability of organo–inorganic hybrid perovskite materials severely limits the commercialization of perovskite-based PDs. In this work, more stable all-inorganic perovskites, CsPbBr(3− x ) Cl x ( x = 0, 1, 2, 3) microplatelets (MPs), were used to fabricate Schottky PDs with a simple vertical structure of ITO/MP/Au. The optimized CsPbBr3 MP Schottky PDs exhibit a rapid response speed (75 μs) and a very low dark current (2 pA) at zero bias. Meanwhile, the device shows a high on/off ratio (>10 6 ), a large specific detectivity (>10 12 Jones) and a linear dynamic range (LDR = 137 dB) with excellent thermal and long-term stability. Furthermore, a tunable spectral response from the ultraviolet to visible range is also demonstrated. These results provide a simple avenue to realize self-driven and spectrally tunable all-inorganic perovskite Schottky PDs with good stability.